Reprint of "Decision-making in child protective services: Influences at multiple levels of the social ecology". (November 2015) - Font, Sarah A.; Maguire-Jack, Kathryn
Abstract: Decision-making in the child protection system is influenced by multiple factors; agency and geographic contexts, caseworker attributes, and families' unique circumstances all likely play a role. In this study, we use the second cohort of the National Survey of Child and Adolescent Well-Being to explore how these factors are associated with two key case decisions—substantiation and removal to out-of-home care. Analyses are conducted using weighted hierarchical linear models. We find that substantiation is strongly influenced by agency factors, particularly constraints on service accessibility. Substantiation is less likely when agencies can provide services to unsubstantiated cases and when collaboration with other social institutions is high. This supports the concept that substantiation may be a gateway to services in some communities. Agency factors contributed less to the probability of removal among substantiated cases, though time resources and constraints on decision-making had some influence. For both substantiation and removal risks, county, caseworker, and child characteristics were less influential than agency characteristics and family risk factors.